'Men Actually Need to Practice the Conversation': Collective Learnings from Australian Programs Seeking to Challenge Outdated Masculine Stereotypes and Norms. Issue 1 (March 2023) - Stewart, Rebecca; Roberts, Steven; Wright, Breanna; Smith, Liam
Programs working with men and boys in relation to gender equality are increasing. Little is known, however, about how these programs go beyond raising awareness, to supporting attitude and behaviour change in their participants. In response, 17 facilitators from eight Australian organisations were interviewed to identify program design and delivery strategies that increase male participants' engagement. Analysis of interview data revealed three themes and seven subthemes, which were crosschecked against survey data from 79 program participants. The themes were the provision of a safe, judgement-free environment; encouraging and supporting growth in participants; and the central role of the facilitators in the success of the first two themes, and in the delivery of programs more generally. Facilitator and participants held mostly consistent perspectives, which were comparable with the existing literature; variations from the literature were noted, however, regarding the lack of efficacy of single-session programs and the relevance of facilitator gender.